1986
DOI: 10.1159/000183990
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor Resident Peritoneal Macrophages and Peritonitis Incidence in Continuous Ambulatory Peritoneal Dialysis

Abstract: Our study was designed to see if peritoneal macrophages (PM) of continuous ambulatory peritoneal dialysis (CAPD) uremic patients, by weaking local defense, could contribute to an increase of peritonitis incidence. Coincubation of nonadherent control responding cells (NACRC) and PM from normal subjects or CAPD patients with low peritonitis incidence (LPI) did not modify blastogenic response of cells to PHA. Coincubation of NACRC and PM from CAPD patients with high peritonitis incidence (HPI) produced noticeable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This may cause a decreased production of stimulating factors (interleukin-1, leukotriene A) which could inhibit lympho-monocyte activation, thereby reducing the release of interleukin-2 and interferon-gamma. The sequence of these immunological events has been studied in our laboratory and the results confirm these pathophysiological hypotheses [27]. In patients with a high peritonitis incidence, the production of interferon-gamma by peri toneal lymphocytes and of interleukin-1 by peritoneal macrophages was significantly de creased, while the release of prostaglandin E2 was increased, when compared to CAPD pa tients with low rates of peritonitis or healthy subjects ( fig.…”
Section: ]supporting
confidence: 59%
See 1 more Smart Citation
“…This may cause a decreased production of stimulating factors (interleukin-1, leukotriene A) which could inhibit lympho-monocyte activation, thereby reducing the release of interleukin-2 and interferon-gamma. The sequence of these immunological events has been studied in our laboratory and the results confirm these pathophysiological hypotheses [27]. In patients with a high peritonitis incidence, the production of interferon-gamma by peri toneal lymphocytes and of interleukin-1 by peritoneal macrophages was significantly de creased, while the release of prostaglandin E2 was increased, when compared to CAPD pa tients with low rates of peritonitis or healthy subjects ( fig.…”
Section: ]supporting
confidence: 59%
“…The above-mentioned studies have shown that in CAPD patients with a high peritonitis incidence the production of inter feron-gamma by peritoneal lymphocytes is reduced compared to the values observed in patients with a low peritonitis rate or in nor mal subjects [27], In trying to correct this (fig. 23).…”
Section: Over the Past Years It Has Become Increas Ingly Evident Thatmentioning
confidence: 98%
“…Development of new connection devices has reduced the incidence of peritonitis considerably, but recurrent infection remains a significant source of morbidity and a frequent cause for termination of CPD. Because it had been previously reported that peritoneal macrophages from some CPD patients are deficient in their ability to produce inflammatory mediators such as cytokines, we examined the possibility that this defect might reflect a systemic defect in mononuclear cell function [1,2]. Although there was significant variability among patients, the median Sis for IL-I[~ and TNF-cz mRNA levels were similar for PBMC of CPD patients and controls, as were the amounts of stimulated TNF-cz protein secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal macrophages from some CPD patients have been shown to have a decreased ability to secrete cytokines such as interleukin-1 [3 (IL-I~) and tumor necrosis factor-ct (TNF-c0 [1,2]. These cytokines are critical to the development of an appropriate inflammatory response to bacteria and thus a defect in cytokine secretion by peritoneal macrophages could predispose a patient to develop peritonitis.…”
Section: Mononuclear Cellmentioning
confidence: 99%